The prospects and challenges of the e-Cash services by Bank Islam at Universiti Utara Malaysia / Norhayati Baharum - Baharum, Norhayati (Faculty of Business Management, 2005)
The study was done to identify the potentials and challenges to introduce and promote the use of electronic payment as an alternative payment in Malaysian society. The study is an attempt to provide greater comprehension to the services of e-Cash as an alternative payment. With Bank Islam as service provider, the e-Cash services was launched at 'Universiti Utara Malaysia' on September 2004 and the application was added to the student's University Multi Purpose Card (UMPC). Questionnaires were distributed conveniently to the students, staffs, and merchant in the campus and cater to 100 respondents. Face to face interview was conducted with the Senior Manager of Electronic Banking Department at Bank Islam to gain more information from the service provider's point of view. Analysis shows that the e-Cash services has a lot of potential as it is available to all Bankcard holders in Malaysia, which now amounted to about 13 million people. The respondents had argued the issue of security of the services, while most of them did not refuse to use the services if they had chances. Accessibility and security appeared to be the most critical factors that influences customer to use the services. It is recommended to the Bank to have full string promotion to convince customer to use the service and maintain the accessibility; the reloaded machineries and numbers of merchants whose offer the e-Cash Payment.